The Relationship Between Motivation, Axiety, and English Proficiency at Pusdiklat Keuangan Umum Jakarta - Indrawati, Efi Dyah (UICELL, 2017)
The study analyses motivation and anxiety in relation to the English proficiency of trainees of English at Pusdiklat Keuangan Umum (PKU) Jakarta. Based on a survey consisting of AMTB questionnaire, FLCAS questionnaire, and the result of English proficiency test, the findings revealed that there were a high level of motivation and moderately high level of anxiety in learning English among PKU trainees, as well as an intermediate level of English proficiency. Also, motivation was more significant than anxiety in influencing English proficiency, but both variables were found to have not a very strong relationship with it, which is only 0.291 to affect on English proficiency. Therefore, based on goodness of fit statistics, there should be variables other than motivation and anxiety to be put in the regression model. Finally, the study puts several suggestion and recommendations for teachers, training center, and future researchers in the area.